1998
DOI: 10.1111/j.1365-2621.1998.tb15860.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Characteristics of Soymilk and Tofu Made from Lipoxygenase‐Free and Normal Soybeans

Abstract: Soymilk made from lipoxygenase-free soybeans had less cooked beany aroma, less cooked beany flavor and less astringency and was rated darker and more yellow than that made from soybeans with normal lipoxygenase. Sensory descriptive panelists noted no differences between lipoxygenase-free and normal soybeans for milky flavor, wheat flavor, thickness, chalkiness or aftertaste. Tofu made from lipoxygenase-free soybeans had less cooked beany flavor than that made from normal soybeans. There were no differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 22 publications
(21 reference statements)
4
51
0
15
Order By: Relevance
“…Despite the emphasis in the literature placed on the rejection of soy beverages due to flavor (TORRES-PENARANDA; REITMEIER, 2001;TORRES-PENARANDA et al, 1998;POTTER et al, 2007;BEHRENS;SILVA, 2004), the aftertaste was reported as the least desirable characteristic (20 and 11% of cases, respectively) only for beverages B and C (Table 3). The attribute flavor was mainly reported as positive for beverages A, B, C, and D. Flavor was reported as a negative characteristic only for sample E (70 and 17% reported its flavor and salty taste, respectively) (Table 3).…”
Section: Acceptance Of Commercial Beveragesmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the emphasis in the literature placed on the rejection of soy beverages due to flavor (TORRES-PENARANDA; REITMEIER, 2001;TORRES-PENARANDA et al, 1998;POTTER et al, 2007;BEHRENS;SILVA, 2004), the aftertaste was reported as the least desirable characteristic (20 and 11% of cases, respectively) only for beverages B and C (Table 3). The attribute flavor was mainly reported as positive for beverages A, B, C, and D. Flavor was reported as a negative characteristic only for sample E (70 and 17% reported its flavor and salty taste, respectively) (Table 3).…”
Section: Acceptance Of Commercial Beveragesmentioning
confidence: 99%
“…The samples were placed in an accessory determined by the Tukey test (at 5% significance level). Internal preference mapping was obtained for the overall acceptability data matrix by SENSTOOLS 2.3.28 software package (OP&P PRODUCT RESEARCH, 1995-1998. The preference space was defined using the Multidimensional Scaling technique associated with Hierarchical Cluster Analysis (OLIVEIRA et al, 2004).…”
Section: Physical and Chemical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Em outro estudo com SC e SCLL para obtenção de extratos de soja de TORRES-PENARANDA et al 19 , foi verificada, nos extratos de soja obtidos de SCLL, menor intensidade para o sabor de "feijão cru", pelos provadores americanos do que pelos chineses quando comparados ao extrato de soja obtido de SC, ao passo que os japoneses não encontraram diferença alguma entre ambos os extratos.…”
Section: Avaliação Sensorialunclassified